Comments on “Early Activation of Lung CD8+ T Cells After Immunization with Live Plasmodium berghei Malaria Sporozites” - Samiha Fatima (Pathogens and Immunity)
The recent study by van Schuijlenburg et al [1] suggests that the lungs may serve as an active and previously underappreciated site of T-cell priming following late-arresting genetically attenuated parasites (LA-GAP) malaria vaccination. Their findings channel traditional liver-focused models and open important avenues for understanding the immunological dynamics of whole-sporozoite vaccines.